MHC Class I Chain-Related Gene A Polymorphisms and Linkage Disequilibrium with HLA-B and HLA-C Alleles in Ocular Toxoplasmosis. - Christiane Maria Ayo; Ana Vitória da Silveira Camargo; Fábio Batista Frederico; Rubens Camargo Siqueira; Mariana Previato; Fernando Henrique Antunes Murata; Aparecida Perpétuo Silveira-Carvalho; Amanda Pires Barbosa; Cinara de Cássia Brandão de Mattos; Luiz Carlos de Mattos (PLoS ONE, 2015)
This study investigated whether polymorphisms of the MICA (major histocompatibility complex class I chain-related gene A) gene are associated with eye lesions due to Toxoplasma gondii infection in a group of immunocompetent patients from southeastern Brazil. The study enrolled 297 patients with serological diagnosis of toxoplasmosis. Participants were classified into two distinct groups after conducting fundoscopic exams according to the presence (n = 148) or absence (n = 149) of ocular scars/lesions due to toxoplasmosis. The group of patients with scars/lesions was further subdivided into two groups according to the type of the ocular manifestation observed: primary (n = 120) or recurrent (n = 28). Genotyping of the MICA and HLA alleles was performed by the polymerase chain reaction-sequence specific oligonucleotide technique (PCR-SSO; One Lambda®) and the MICA-129 polymorphism (rs1051792) was identified by nested polymerase chain reaction (PCR-RFLP). Significant associations involving MICA polymorphisms were not found. Although the MICA*002~HLA-B*35 haplotype was associated with increased risk of developing ocular toxoplasmosis (P-value = 0.04; OR = 2.20; 95% CI = 1.05-4.60), and the MICA*008~HLA-C*07 haplotype was associated with protection against the development of manifestations of ocular toxoplasmosis (P-value = 0.009; OR: 0.44; 95% CI: 0.22-0.76), these associations were not statistically significant after adjusting for multiple comparisons. MICA polymorphisms do not appear to influence the development of ocular lesions in patients diagnosed with toxoplasmosis in this study population.